Cooperative Learning with a Game Model: Exploring Students' Speaking Ability About Asking and Giving Suggestions - Fatmasari, Elli; Firdawati, Firdawati (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The purpose of this study was to improve speaking competence through the COLEGA (Cooperative Learning with Game) model for public middle school students. This study was classroom action research. The subjects of the study were 40 students in grade VIII of the public middle school 46 Bekasi. We conducted the study in two cycles, cycle I and cycle II. In the meantime, we collected data by following the steps of classroom action research, which include planning, implementing actions, observing, and reflecting. We used quantitative descriptive analysis to analyze the data. The study's results demonstrated that most students struggled to comprehend and react to the speaker's words. We can conclude that the level of teacher and student activity in the learning process during the two cycles was very high. In cycle 1, the student's learning completeness was 44.18%, and in cycle 2, it increased to 86.04%, with an average score of 69.5 in cycle 1 and 79.13 in cycle 2. Therefore, we conclude that the COLEGA method in grade VIII of public middle school 46 Bekasi has enhanced students' speaking skills in asking and making suggestions.